Breaking Barriers in Higher Education Leadership: Empowering Educational Personnel with the 3M Management Model - Adeoye, Moses Adeleke; Oladimeji, Rasheedat Modupe; Yusuf, Jamilla (LPPM Universitas PGRI Semarang, 2024)
This study aims to explore the potential of the 3M Management Model in empowering educational personnel to break barriers in higher education leadership. The objectives of the study seek to bridge the gap between theory and practice in higher education leadership by exploring the potential of the 3M Management Model and providing evidence-based insights that can inform decision-making and improve leadership development programs. The method used in this research is a Systematic Literature Review. The result found that educational leaders can develop their leadership abilities and encourage constructive change within their institutions by implementing this paradigm. The advantages of using the 3M Management Model are examined on how it can promote an innovative culture, enhance decision-making procedures and boost output. It also emphasizes how critical it is to cultivate a growth mentality, put successful procedures into place and use pertinent metrics to gauge performance. Higher education institutions can overcome obstacles and achieve sustainable growth and success by equipping their staff with this strategy